2016
DOI: 10.18632/oncotarget.12488
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline is an NF-κB inhibitor that induces apoptotic cell death in malignant T-cells

Abstract: Cutaneous T-cell Lymphoma (CTCL) is a rare non-Hodgkin's lymphoma that can affect the skin, blood, and lymph nodes, and can metastasize at late stages. Novel therapies that target all affected disease compartments and provide longer lasting responses while being safe are needed. One potential therapeutic target is NF-λB, a regulator of immune responses and an important participant in carcinogenesis and cancer progression. As a transcription factor, NF-λB targets genes that promote cell proliferation and surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Doxycycline has been reported to have antitumor properties in prostate and breast cancers. 39,40 In addition, the following features of doxycycline have been reported: (1) nonspecific matrix metalloproteinase inhibition; 41 (2) induction of apoptosis; 42 (3) decreasing the expression and transcriptional activity of β-catenin; 43 (4) reversing the epithelial-mesenchymal transition (EMT) by suppressing EMT genes and restoring the expression of E-cadherin; 44,45 (5) causing the G1-S phase cell cycle arrest by stabilizing p53 and p21, and the Fas/FasL cascade; 46 (6) inhibiting the expression and phosphorylation of focal adhesion kinase and thus regulating cell adhesion and migration, reducing the phosphorylation of nuclear factor-κB (NF-κB)/p65, protein kinase B (Akt), and endothelial NOS; 47 (7) inhibiting the activation of VEGF-C signaling; 48 (8) inhibiting tumor necrosis factor-induced NF-κB activation; 49 (9) modulating the ROS-ASK1-JNK pathway; 50 (10) perturbing signal transducer and activator of transcription 3 (STAT3) and ERK activation and increasing proteasome-dependent protein neddylation; 51 (11) eliminating cancer stem cells; 52 and (12) decreasing the concentration of several cytokines. 53 Doxycycline has also been identified to affect the oxygen consumption rate and glycolysis, and hence it has been suggested for the repurposed targeting of energy metabolism in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline has been reported to have antitumor properties in prostate and breast cancers. 39,40 In addition, the following features of doxycycline have been reported: (1) nonspecific matrix metalloproteinase inhibition; 41 (2) induction of apoptosis; 42 (3) decreasing the expression and transcriptional activity of β-catenin; 43 (4) reversing the epithelial-mesenchymal transition (EMT) by suppressing EMT genes and restoring the expression of E-cadherin; 44,45 (5) causing the G1-S phase cell cycle arrest by stabilizing p53 and p21, and the Fas/FasL cascade; 46 (6) inhibiting the expression and phosphorylation of focal adhesion kinase and thus regulating cell adhesion and migration, reducing the phosphorylation of nuclear factor-κB (NF-κB)/p65, protein kinase B (Akt), and endothelial NOS; 47 (7) inhibiting the activation of VEGF-C signaling; 48 (8) inhibiting tumor necrosis factor-induced NF-κB activation; 49 (9) modulating the ROS-ASK1-JNK pathway; 50 (10) perturbing signal transducer and activator of transcription 3 (STAT3) and ERK activation and increasing proteasome-dependent protein neddylation; 51 (11) eliminating cancer stem cells; 52 and (12) decreasing the concentration of several cytokines. 53 Doxycycline has also been identified to affect the oxygen consumption rate and glycolysis, and hence it has been suggested for the repurposed targeting of energy metabolism in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the observation by Alexander-Savino that doxycycline inhibits neoplastic T cell growth by acting as an NF-kappaB inhibitor provides another potential mechanism for the beneficial effect of tetracycline-type drugs for LyP. [30] A clinical trial to determine if long term administration of doxycycline is useful as a suppressive treatment for LyP might be worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive activation of NF-κB is a hallmark of several types of cancers, which not only promotes tumorigenesis and cancer development but also enhances drug resistance (Dolcet et al, 2005 ; Hanahan and Weinberg, 2000 ). Recent reports have shown that inhibition of NF-κB significantly inhibited cancer growth by directly inducing cancer cell apoptosis (Woo et al, 2016 ; Alexandersavino et al, 2016 ; Kwon et al, 2016 ; Yin et al, 2016 ; Hayden et al, 2008 ). Interestingly, the multifunctional tumor associated protein Annexin A2 promotes NF-κB activation via directly binding to NF-κB p50 subunit with its N-terminal sequences, and inhibition of Annexin A2 provides a new regulatory tool on NF-κB activity (Jung et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%